Relationship between National Health Insurance Ownership and Compliance with Access to Health Services for Patients with Severe Mental Disorders (PSMD) “Pasung” in Blitar Regency, Indonesia - Dhimas Anggi Septiansyah; Emi Wuri Wuryaningsih; Fitrio Deviantony (Journal of Community Empowerment for Health, 2023)
Patients with Severe Mental Disorders (PSMD) "Pasung" require long-term care, which causes a financial burden on the family. The Indonesian government has guaranteed funding for the treatment. However, there are still PSMDs who do not make regular visits to health services. This study aimed to describe the Relationship between National Health Insurance Ownership and Compliance with Access to Health Services for PSMDin Blitar Regency, Indonesia. This study used an analytic observational design with a retrospective cohort study approach. Total sampling techniques selected 50 PSMD "pasung" recorded health insurance and several visits to primary health services. The data was obtained from the primary health services reporting records from January to March 2020. This study used the biserial point correlation (CI: 99%) test for analyzing data. This study has ethical clearance approval. The results showed that there was a positive relationship between ownership of NHI and compliance with access to health services (t-obs (3,491) ≥ critical (2,678); p-value = 0,001; r-bis = 0,450; α = 0,01). Indonesia has guaranteed the cost of PSMD treatment with shackles, but patients and families who use these facilities are not optimal. In conclusion, national health insurance ownership is related to compliance with access to health services for PSMD "Pasung". Health agencies can pay attention to policy-making for enhancing access to health services of PSMD "Pasung".